(untitled) (CaJoST, 2023)
Groundnut is an important cash crop produced in large quantity in North-Western Nigeria. The production of ground nut reached its peak in Nigeria during the period of 1969 to 1980s, when approximately 1.7 million tonnes of the pods were produced from an area of 1.9 million hectares. This enormous waste is presently not being harnessed productively in other than burning, which is a major air pollution and indiscriminate dumping that cause environmental hazard. Groundnut husk when burnt under controlled temperature has been found to be rich in silica. The benefit of high silica content makes it very useful pozzolanic material and a good possible admixture in concrete production. Conversion of wastes to wealth is the new vogue all over the world; this is not only to reduce environmental degradation and pollution but also to effectively put these wastes into use that would be beneficial to mankind. This paper investigated the suitability and application of Groundnut Shell Ash (GSA) from Sokoto, Kebbi and Zamfara states as pozzolanic and siliceous partial mineral admixture in cement production for cheaper, improved strength and durability of mortar and concrete making in North-Western Nigeria. Six sandcrete blocks using groundnut shell ash (GSA) as partial cement admixture were investigated for each replacement levels of cement to GSA ration of 100/0%, 90/10%, 80/20%, 70/30%, 60/40%, and 50/50% with groundnut shell ash. The results indicated that the strength of the sandcrete decreases with increase of cement above 20% replacement.